Population dynamics of skipjack tuna (Katsuwonus pelamis) in the northern and western waters of Aceh. Issue 1 (February 2021) - Damora, A; Fazilla, F; Perdana, A W; Rahmah, A; Aprilla, R M; Salmarika, S
Abstract: Skipjack tuna ( Katsuwonus pelamis ) is a pelagic fish species that have important economic value in the northern and western waters of Aceh. Skipjack tuna is one of the dominant catch fish landed at the Fishing Port of Kutaraja, Banda Aceh. The dynamics population of skipjack tuna in the northern and western waters of Aceh need to be done to get information on the status of skipjack tuna in ocean. This research aims to determine the dynamic parameters of the population of skipjack tuna based on the growth parameters, length and weight relationship, length distribution, length at the first capture, mortality, and exploitation rate. The data collection was conducted in February to March 2020, located at the Fishing Port of Kutaraja, Lampulo, Banda Aceh. A total of 166 sample, were measured with stratified random sampling method. The FAO-ICLARM Stock Assessment Tools (FiSAT) program was used by analyze growth parameter, mortality parameters, and exploitation rate. The results showed that has a negative allometric growth pattern, with a length of fork length (FL) ranging from 25-51 cm. The length of first capture was 38, 2 cm. The asymptotic length (L∞) of skipjack tuna was 84, 78 cm with K value of 0.22/year and. The estimated natural mortality (M), fishing mortality (F), and total mortality (Z) were 0, 5/year, 1.55/year, and 2.99/year respectively. The exploitation rate (E) of skipjack tuna was 0.83/year that indicated skipjack tuna in the Northern and Western waters of Aceh over-exploited.